Inertia in health care organizations: A case study of peritoneal dialysis services. Issue 3 (July 2015) - Wang, Virginia; Lee, Shoou-Yih D.; Maciejewski, Matthew L.
Abstract : Background: Change is difficult for health care organizations where adoption of new practices is notoriously slow. Inertial behavior may reflect organizations' rational, strategic nonresponse to its environment or latent, institutionalizing preservation of dominant organizational routines and norms. Such strategic and selective influences of organizational inertia have different implications on the efficacy of policy to induce intended change. Purpose: The aim of this study was to examine whether strategic and selective factors were associated with the provision of peritoneal dialysis (PD) services in outpatient dialysis facilities in the United States between 1995 and 2003. Approach: We conducted a longitudinal retrospective study of all outpatient end-stage renal disease dialysis facilities, using 1995–2003 administrative data from the U.S. Renal Data System. Findings: Less than half of U.S. dialysis facilities offered PD, and this pattern was stable despite substantial growth of dialysis facilities entering the market. We found little support for strategic influences and some evidence that selective factors were predictive of dialysis facilities' PD provision. Practice Implications: Although the design of many policy and health care reform efforts widely accepts the strategic perspective of altering incentives and the environment to induce change, the presence of selective inertial influences raises concerns about the efficacy of policy intervention in the face of institutionalized organizational behavior that may be less amenable to policy intervention. Incentives recently introduced by Medicare to increase facility provision of PD may be less effective than might be expected.